Case report: Unilateral pulmonary artery agenesis and Kommerell's diverticulum in 1-year old girl - Miseviciene, Valdone; Liakaite, Gintare; Zaveckiene, Jurgita; Snipaitiene, Ausra (Frontiers in Pediatrics, 2023)
Background: Unilateral pulmonary artery agenesis (UPAA) and Kommerell’s diverticulum (KD) are two rare embryologically unrelated congenital vascular malformations rarely diagnosed in children. This is the first report of our knowledge of the unique combination for a child as patients are at a high risk of pulmonary hypertension and rupture of the diverticulum. Our aim is to present the case of a pediatric patient with UPAA and KD with the short literature review and to highlight the importance of early diagnostics of rare congenital vascular malformations. Case report: A 1-year-old girl presented to the emergency department with prolonged cough and variable wheezing. A hypoplastic left lung was suspected in the radiographic image of the chest. A transthoracic echocardiogram revealed absence of the left pulmonary artery and right arch of aorta and anomaly of subclavian arteries was suspected. The diagnosis was confirmed by computed tomography scans of the chest that demonstrated elongation of the aorta and an aberrant right subclavian artery with KD, as well as absence of the left pulmonary artery. The patient is being followed up for the development of pulmonary hypertension and compression of vascular structures to the airways as well as any indications for surgical intervention because of the KD. Conclusions: UPAA and KD are two very rare congenital vascular anomalies usually diagnosed in adults. A high risk of pulmonary hypertension and rupture of diverticulum is noted for adult patients. This case provides us with an exclusive possibility to follow up a patient with an extremely rare combination of the two vascular anomalies with insufficiently known future complications and outcomes.